Cost reduction approaches for fermentable sugar production from sugarcane bagasse and its impact on techno-economics and the environment - Baral, Pratibha; Munagala, Meghana; Shastri, Yogendra; Kumar, Vinod; Agrawal, Deepti (Springer, 2021)
In an enzymatically driven lignocellulosic biorefinery, pretreatment and hydrolysis modules are the two most significant cost contributors for obtaining high gravity sugar solutions. The present study aimed to reduce the use of alkali and Cellic CTec2 during the bioprocessing of sugarcane bagasse (SCB). Later its impact on the overall process economics and the environment was evaluated. During pretreatment, solid loading of 15% (w/w) and use of 2% (w/v) sodium hydroxide at 121 °C for 30 min emerged as an optimum strategy. It resulted in > 65% delignification of SCB, retaining ≥ 90% and 65% of glucan and xylan fraction, respectively, in the pretreated biomass. Two approaches were evaluated in parallel to minimize the requirement of this commercial cellulase enzyme blend. The first strategy involved its partial replacement with an in-house enzyme cocktail by blending. The second route was performing hydrolysis with reduced loadings of cellulase enzyme blend above its optimum temperature, which gave more promising results. Hydrolysis of 20% alkali pretreated SCB with cellulase enzyme blend dosed at 15 mg protein g−1 glucan led to 84.13 ± 1 and 83.5 ± 2.3% glucan and xylan conversion yields respectively in 48 h at 52.5 °C. The filtrate and wash fraction contained ≥ 165 and ≥ 65 g L−1 sugar monomers representing glucose and xylose. However, in both the fractions > 75%, sugar accounted for glucose. The techno-economic analysis revealed that the sugar production cost from SCB was 1.32 US$/kg, with the optimized bioprocess. Environmental impact study showed that the process contributed to 1.57 kg CO2 eq in terms of climate change.
Keywords: Sodium hydroxide pretreatment; Sugarcane bagasse; High-solids enzymatic saccharification; Techno-economic analysis; Life cycle assessment